Ecological information: definitions and determinations - Проскура, Ганна Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The paper analyzes the «environmental information» category, the etymology of the word, approaches to its definition, the main features and characteristics. Author defines the main approaches to the understanding of the term «environmental information» in the law and science in sphere of access to environmental information. One of the crucial problems is an issue of providing every individual with the right for information as the fundamental constitutional right. One of the crucial problems is an issue of providing every individual with the right for information as the fundamental constitutional right. Article 34 of the Constitution of Ukraine guaranties everybody the right for free collecting, keeping, use and extension information orally, in written form or in any other form at one’s option. Despite big quantity of scientific literature in this sphere, some actual issues of providing every individual with the right for access to ecological information still have to be studied. Legal aspects of access to ecological information have been studied by these scientists: V.I.Andreytsev, G.I.Balyuk, A.P.Getman, V.I.Gordeev, I.I.Karakash, N.R.Kobetska, V.V.Kostytskyi, S.M.Kravchenko, V.I.Kutuzov, M.V.Krasnova, N.R.Malysheva, A.A.Popov, E.V.Poznyak, I.V.Sukhan, Y.S.Shemshuchenko, M.V.Shulga and the other scientists. The primary problem is to define the term “ecological information” and formation the main approaches to understanding given category. It is also actual to set the role of ecological information and its determination. It is proposed in this article to consider the category “ecological information” as the need of detailed study, analyzing and research of legal base of human right for access to ecological information that is: the legal nature of the given right and legislation in this sphere, still exists. The goal of the article is analyzing the category “ecological information” in the science and the Legislation of Ukraine. At the domestic level the regime of ecological information is defined by the Constitution of Ukraine, the Laws of Ukraine “About Preservation of Natural Amenities”, “About Information”, “About Access to Public Information”, “About Public Appeals” and the other laws and implementing regulations. Internationally legal regime of ecological information is defined, first of all, by Orukh Convention Directive 2003/4/ЄЕС of European Parliament and Council of 28 January 2003 р., «The UNECE Convention on Access to Information, Public Participation in Decision-making and Access to Justice in Environmental Matters, usually known as the Aarhus Convention etc. The norms that regulate issues of access to information can be found in specialized directives of EU. The article analyzes category “ecological information”, etymology of the term, approaches to its definition, the main characteristics and distinctions. The author defines the main approaches to understanding the term “ecological information” in legislation and science, its place in the sphere of access to ecological information. The author recommends focusing on the determinations of the category “ecological information” and defines the main features, and makes conclusion that there is not simultaneous idea on components, the subject and determinations of the given category among the definitions of scientific concept “ecological information”. Access to ecological information has to be considered in the context of social utility; because, mainly, access to ecological information about environment aims to provide constitutional rights and ecological interests of citizens. That is why it is of great importance to give complete, public, meaningful, well-timed and objective definition of ecological information.